Effect of Fluorinated Anion on the Physicochemical, Rheological and Solvatochromic Properties of Protic and Aprotic Ionic Liquids: Experimental and Computational Study. Issue 35 (15th December 2017) - Sharma, Gyanendra; Singh, Dharmendra; Gardas, Ramesh L.
Abstract: The essential properties of ionic liquids (ILs) for various applications can be tuned by changing the combination of cations or anions in ILs. This work demonstrates how the structure variations effect the physicochemical, rheological and solvatochromic properties of protic and aprotic ionic liquids. For this, a set of four ionic liquids have been synthesized and characterized through spectral techniques. Thermal stability and phase behaviour of ILs have been analyzed by TGA and DSC. The experimental density, speed of sound and viscosity have been measured as a function of temperature from 293.15 to 343.15 K and an attempt has been made to distinguish the crucial role of counter ions on measured properties. Further, the fluidity and polarity behaviour of hydroxyl ammonium based protic or 1‐alkyl‐1, 2, 4‐triazolium based aprotic cation and fluorinated anions were investigated through their rheological and polarity parameters at 298.15 K and discussion have been made on the basis of columbic and hydrogen bonding interactions. Interestingly, we found that anions have dominant effect on studied physicochemical properties irrespective of protic/aprotic nature of ionic liquid while the contribution of cations were vital for solvatochromic and rheological properties. Additionally, the ion‐pair interaction energy, dipole moment and hydrogen bonding interactions of studied ILs have been analysed using density functional theory (DFT) calculations to support the experimental findings. Abstract : Effect of structure variation on physicochemical and solvatochromic properties have been analyzed through experimental and computational methods. Two different cation and anion have been scrutinized and found that anion have dominant effect for physicochemical properties while cation plays significant role for solvatochromic and rheological properties.